Unregistered Marriage among University Students: Family Influence, Religious Legitimacy, and the Negotiation of Marriage Law - Muis, Moch. Zulkarnain; Hidayati, Nunuk; Kusumo, Muhammad Trenggono (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
Unregistered marriages (nikah siri) are often placed within a rigid dichotomy between religious legitimacy and state legality. However, the lived experiences and legal awareness of those involved are frequently overlooked. This article examines the motives, meanings, and lived experiences of unregistered marriage practices among undergraduate students at Sunan Ampel State Islamic University Surabaya, Indonesia. This article is an empirical legal study that employs a socio-legal approach grounded in phenomenological theory. By engaging three married students, selected through purposive sampling, data were collected via in-depth interviews and analyzed using phenomenological reduction—including bracketing and eidetic reduction—to uncover the essential structure of the participants’ consciousness. This article demonstrates that unregistered marriage is not perceived as a legal violation but rather as a contextual response to the religious, social, and economic conditions faced. The primary motives identified include avoiding adultery, preserving family honor, and achieving economic efficiency. Participants interpret an unregistered marriage as valid under religious law, even though it is not recognized by the state, reflecting a dualism between religious legitimacy and legal validity. In practice, the fulfillment of the rights and obligations of husband and wife is negotiated contextually based on agreement, responsibility, and spiritual commitment, including in decisions to postpone living together and pregnancy. This article argues that unregistered marriages among students are not entirely based on defiance of state law but rather a solution to social conflicts within families